Development and Validation of the Chinese Version of the Quality of Recovery-40 Questionnaire - Chen Y (Dove Medical Press, 2020)
Yeyang Chen,1,2,* Junfu Wang,1,* Siyu Liu,1 Weikun Lai,1 Jinlu Liu,1 Zhen Wang,1 Bopei Li,1 Yuantian Mao,1 Ye Wang,1 Guofei Deng,1 Junqiang Chen1 1Department of Gastrointestinal Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 2Department of Gastrointestinal Surgery, The Sixth Affiliated Hospital of Guangxi Medical University, Yulin, Guangxi Zhuang Autonomous Region, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junqiang Chen Department of Gastrointestinal SurgeryThe First Affiliated Hospital of Guangxi Medical University, 6 Shuangyong Road, Nanning, Guangxi 530021, People’s Republic of ChinaTel +86 771-5356552Email gxhans@163.comPurpose: The present study aimed to develop the official Chinese version of the QoR-40 (QoR-40C) and to test its reliability, validity, and responsiveness.Patients and Methods: A systematic translation procedure was established and performed to develop the QoR-40C from the original English QoR-40 version. After the pilot study, 223 surgical patients were administered  the QoR-40C at four time points. The validity, reliability, and responsiveness were assessed to validate the QoR-40C.Results: The test–retest reliability of the QoR-40C in the morning and afternoon of the third day after surgery was 0.917 (P < 0.001). The split-half reliability for all domains was 0.938 in the morning of the third day after surgery. The median item-to-own dimension and total score of Cronbach’s α for internal consistency of the QoR-40C at different assessment time points were more than 0.70. All the correlation coefficients between each subscale and the QoR-40 total score showed good correlation and were greater than those for other subscales in the morning of the third day after surgery. Furthermore, in the morning of the third day after surgery, the QoR-40C total score was moderately positively correlated with the SF-36 score (ρ = 0.575, P < 0.001), while the QoR-40C score was negatively correlated with the visual analogue scale (VAS) score (ρ = − 0.299, P < 0.001). The factor loadings of each item were within the required range. A statistically significant difference was observed in the QoR-40C total scores before and after the surgery (P < 0.001) with the standardized responsive mean (SRM) of 0.51.Conclusion: The QoR-40C showed good reliability, validity, and responsiveness and was appropriate to be used as a quality of life measurement questionnaire for patients after surgery in China.Keywords: China, quality of life, questionnaire, validity, reliability, responsiveness